(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Climate change has become one of the most critical environmental challenges of the 21st century. Rising global temperatures, altered precipitation patterns, and increased frequency of extreme weather events are profoundly affecting ecosystems and species distribution. This paper examines the relationship between climate change and biodiversity loss, highlighting the mechanisms through which environmental changes disrupt ecosystems, species interactions, and habitat stability. Furthermore, it explores strategies for mitigating biodiversity loss, including conservation policies, ecosystem management, and international cooperation. Understanding these dynamics is essential to preserving ecological integrity and ensuring the sustainability of human societies.